Neurological events with tumour necrosis factor alpha inhibitors reported to the Food and Drug Administration Adverse Event Reporting System. Issue 4 (26th June 2013) - Deepak, P.; Stobaugh, D. J.; Sherid, M.; Sifuentes, H.; Ehrenpreis, E. D.
Summary: Background: The association between inhibition of tumour necrosis factor alpha (TNF‐α) and new onset of neurological adverse events (AEs) is unclear. Aims: To evaluate neurological AEs with TNF‐α inhibitors reported to the Food and Drug Administration Adverse Event Reporting System (FAERS) utilising a standardised scoring tool for drug‐induced AEs. Methods: A search of FAERS for neurological AEs (January 1, 2000 to December 31, 2009) reported with infliximab, adalimumab, certolizumab and etanercept was performed. Full‐text reports were accessed using the Freedom of Information Act and scored using Naranjo score, while accounting for temporal association, previous conclusive reports of the neurological AE with any TNF‐α inhibitor, and alternate explanations including underlying disease, concomitant medications and comorbidities, such as diabetes mellitus. Results: There were 772 reports. Most were in patients who had rheumatoid arthritis (393, 50.9%) followed by inflammatory bowel disease (140, 18.1%). No significant differences in age or gender were seen between IBD patients compared with rheumatological diseases ( P  = 0.584 and P  = 0.055 respectively). Etanercept was reported most (327, 42.4%) followed by infliximab (276, 35.8%) ( P  = 0.008). Peripheral neuropathy was the most common neurological AE (296 reports, 38.3%) followed by central nervous system and/or spinal cord demyelination (153 reports, 19.8%). Majority (551, 71.4%) of the reports were of 'possible' AE with the remaining 'probable' AE and none identified as 'definite' AE. Conclusion: While several neurological AEs have been described, definite association between de novo development of these AEs and exposure to TNF‐α inhibitors was not established using the Naranjo score.